2021
DOI: 10.1177/10783903211023565
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Reported Burden in RE-KINECT: Data From a Prospective Real-World Tardive Dyskinesia Screening Study

Abstract: Background: RE-KINECT (NCT03062033), a real-world study of possible tardive dyskinesia (TD) in antipsychotic-treated patients, included a questionnaire to assess the effects of patients’ abnormal involuntary movements on caregivers. Objective: To capture the experiences of caregivers who assisted individuals with abnormal involuntary movements that were confirmed by clinicians as being consistent with TD. Methods: Qualified (nonpaid) caregivers were invited to complete a questionnaire that included the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…For example, data from the RE-KINECT study indicate that TD places a significant burden on caregiver daily activities, productivity, and ability to socialize. 32 These findings also do not account for recent advances in the treatment of TD, notably the approval of vesicular monoamine transporter 2 inhibitors in the United States. 33 While these agents have been shown to be clinically effective, it remains to be determined whether their use will impact the associated economic burden.…”
Section: Discussionmentioning
confidence: 96%
“…For example, data from the RE-KINECT study indicate that TD places a significant burden on caregiver daily activities, productivity, and ability to socialize. 32 These findings also do not account for recent advances in the treatment of TD, notably the approval of vesicular monoamine transporter 2 inhibitors in the United States. 33 While these agents have been shown to be clinically effective, it remains to be determined whether their use will impact the associated economic burden.…”
Section: Discussionmentioning
confidence: 96%
“… 51 Notably, among patients with at least one psychiatric disorder who have three or more months of lifetime antipsychotic exposure, those with TD have lower rates of employment than those without. 53 In addition, patients may experience difficulties in carrying out daily activities necessary for independent living because of their symptoms. 54 …”
Section: Diagnosis Of Tdmentioning
confidence: 99%
“…104 The burden of TD affects not only the patients themselves, but extends to their caregivers, as described in the RE-KINECT study, in which caregivers reported that the TD symptoms of the patient in their care impacted their own ability to continue usual activities (50.0%), be productive (58.3%), socialise (55.6%) and take care of themselves (50.0%). 53 To date, there are no Japanese studies that specifically investigate TD caregiver burden, but it is reasonable to expect that caregivers in Japan face similar issues.…”
Section: Therapeutic Advances In Psychopharmacologymentioning
confidence: 99%
“…4 , 5 TD carries a debilitating social and functional burden for both patients and caregivers. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…4,5 TD carries a debilitating social and functional burden for both patients and caregivers. 6,7 Knowledge of TD among Japanese physicians is limited, and they may not fully understand the importance of monitoring for this drug-induced movement disorder among patients treated with antipsychotics. An understanding of how to effectively manage patients and when to initiate treatment once diagnosed may also be lacking.…”
Section: Introductionmentioning
confidence: 99%